Association between famine exposure in early life and risk of hospitalization for heart failure in adulthood - Chen, Chao-lei; Wang, Jia-bin; Huang, Yu-qing; Feng, Ying-qing (Frontiers in Public Health, 2022)
Background Few studies have reported the association of early life exposure to famine with the risk of heart failure. The current study aimed to investigate whether exposure to famine in early life is associated with a higher risk of hospitalization for heart failure in adulthood. Methods We used data from participants included in the sub-cohort of the China Patient-centered Evaluative Assessment of Cardiac Events Million Persons Project in Guangdong Province. Specific years of birth were used to define the famine-exposed group (born during the famine of 1959–1962), the pre-famine group (born before the famine [1954–1957], and the post-famine group (born after the famine [1964–1967]). Multivariable-adjusted generalized linear models were used to examine the associations of early life famine exposure with the risk of hospitalization for heart failure. Results A total of 36,212 participants were enrolled in this analysis with a median age of 57.4 years and 37.5% of them were men. Compared with the post-famine group, famine births and pre-famine births were associated with increased risk of heart failure (OR: 1.96 [1.56–2.48] and OR: 1.62 [1.07–2.47], respectively). When compared with the age-balanced non-exposed group, the famine-exposed group was also significantly associated with increased risk of heart failure (OR: 1.32 [1.11–1.57]). The associations were stronger in participants with better economic status and in participants with hypertension, diabetes, and dyslipidemia (P for interaction < 0.05). Conclusion Early life exposure to the Chinese famine is associated with an elevated risk of hospitalization for heart failure in adulthood.